EFEKTIVITAS PENYULUHAN LSM JARINGAN NELAYAN (JALA) TENTANG PENGOLAHAN MANGROVE TERHADAP IBU RUMAH TANGGA DI KAMPUNG TANJUNG BATU KECAMATAN PULAU DERAWAN KABUPATEN BERAU - Royan Aditya Pratama; Said Abdussyahid; Heru Susilo (Jurnal Pembangunan Perikanan dan Agribisnis, 2022)
This study aimed at knowing the effectiveness of community outreach conducted by LSM Jaringan Nelayan/JALA (CSO of Fishermen’s Network) about managing mangroves on homemaker in Tanjung Batu Village, Pulau Derawan Sub-district, Berau Regency. The primary data collection was conducted in March 2020 in Tanjung Batu Village, Pulau Derawan Sub-district, Berau Regency; the primary data collection through the interview was done using the list of questions arranged based on the study objective. The sampling method referred to the census method with a total sample of 15 homemakers taken during the training on mangroves, and they were interviewed as the respondents. The result showed that the indicators of clarity for the objective, analysis process and policy formulation, careful planning, and the program arrangement were in the moderate category, while the indicators of clarity for the strategy, the availability of facilities and infrastructures, effective implementation, and supervision and control system were in the high category. The effectiveness level of the community outreach in achieving the goals in Tanjung Batu Village was entirely in the high category with a mean score of 62.38 at the estimated value of 58-72.